Kendali Penumpang Otomatis Transportasi Bus Menggunakan Near Field Communication Berbasis Internet of Things - Frischa Razzaq Praditya; Dahlia Widhyaestoeti; Andik Eko Kristus Pramuko (Universitas Widyatama, 2021)
Automatic Passenger Control of Bus Transportation Using Near Field Communication Based on Internet of Things. Automatic bus transportation passenger control is a system that helps control the number of bus passengers. This system consists of a series of Arduino Mega 2560 microcontrollers, NodeMCU connected to the existing wifi at each bus stop. NFC reader PN532 as a reader of the NFC tag which functions as a passenger id. Passengers boarding the bus must tap the NFC tag on the NFC reader on the bus. The system counts the number of passengers who tap. When the passenger gets off the NFC tag must be on tap back on the NFC reader, the system automatically reduces the number of passengers on the bus. Data processed by the system displayed in the form of information on the LCD on the bus. The results of this study indicate that the sample tag has been successfully read by NFC reader. The data is then processed by the system and stored in a database.